EVALUASI PELAKSANAAN PEMUNGUTAN PAJAK BUMI BANGUNAN PERDESAAN DAN PERKOTAAN DI KABUPATEN BENGKALIS TAHUN 2017-2018 - ", Syariah; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Based on Law Number 33 of 2004 concerning the financial balance between the central government and regional governments, one of the sources of regional original income is local taxes. Bengkalis is a city that has a promising regional potential, one of which is PBB-P2. However, regional revenues that have been relying on the oil and gas sector continue to decline. As for the formulation of the problem in this research is how the implementation of land and building tax collection at the Bengkalis Regency Regional Revenue Agency in 2017-2018 and what are the inhibiting factors.This research was conducted with the aim of describing the evaluation of rural and urban land and building tax collection in Bengkalis Regency in 2017 and 2018. This research is a descriptive study with a qualitative approach. The data collection techniques used were observation, interview and documentation. The data analysis technique used is descriptive and qualitative methods.The results of the study illustrate that the evaluation of the collection of Rural and Urban Land and Building Tax in Bengkalis Regency in 2017 and 2018 uses six evaluation criteria indicators, namely effectiveness, efficiency, adequacy, leveling, responsiveness, and accuracy. From all these aspects, it can be seen that the implementation of the collection on each indicator has been carried out but has not run optimally. As for the inhibiting factor for the low revenue from PBB-P2 from an internal perspective, it is the lack of human resources in the part of the PBB-P2 bailiff and the PBB-P2 assessor, the non-delivery of the Taxpayer Tax Return (SPPT) to taxpayers and the weak application of sanctions. Meanwhile, internal factors are the lack of awareness of paying taxes and the number of taxpayers who live outside the city. Keywords: PBB-P2, Effectiveness, Efficiency, Adequacy, leveling, Responsiveness, Accuracy